DEVELOPMENT OF A MATHEMATICS TEACHING MODULE BASED ON SASAK ETHNOMATHEMATICS WITH A CRT APPROACH TO IMPROVE ELEMENTARY SCHOOL STUDENTS' MASTERY OF GEOMETRY CONCEPTS: Nusa Tenggara Barat, Indonesia - Hasanah, Huswatun; Waluyo, Edy; Supiyati, Sri (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to develop a mathematics teaching module based on Sasak ethnomathematics using the CRT approach to improve elementary school students' mastery of geometric concepts. This study used the Plomp development model, with stages including preliminary research, prototype creation, and assessment. The subjects were sixth-grade elementary school students. The instruments used included interviews, student response questionnaires, observations, test sheets, expert validation, and practicality and effectiveness instruments. The results showed that the developed teaching module met the criteria of validity, practicality, and effectiveness. The module's validity was obtained from expert assessments on material and language, with the module categorized as very adequate. The module's practicality was demonstrated through positive responses from teachers and students, who stated that the module was easy to understand, engaging, and helpful in the learning process. The module's effectiveness was evident in the increase in elementary school students' mastery of geometric concepts after using the module, as demonstrated by the results of the N-gain test, which categorized as moderate or effective. Therefore, the Sasak ethnomathematics-based mathematics teaching module using the CRT approach is effective in improving elementary school students' mastery of geometric concepts. Keywords: Teaching Module, Sasak Ethnomathematics, CRT, Mastery of Geometry Concepts